Experimental assessment of variant selection rules for grain boundary α in titanium alloys. (1st January 2016) - Shi, R.; Dixit, V.; Viswanathan, G.B.; Fraser, H.L.; Wang, Y.
Abstract: In titanium alloys, variant selection (VS) of grain boundary α (GB α ) at prior β grain boundaries (GBs) during α precipitation has a significant influence on the subsequent transformation pathway and transformation texture development of the α phase, and thus on the final mechanical properties. In this paper, we assess systematically the applicability of all current empirical rules for VS of GB α at prior β GBs using experimental characterization of GB misorientation, boundary plane inclination, and orientation relationships between the GB α and adjacent β grains in Ti-5553. We find that all these VS rules may be violated for a given β grain boundary. Based on the experimental observations, the frequencies of each of these empirical rules being either violated or followed have been assessed, and from this assessment, we analyze theoretically whether the arguments underlying each of these rules are physically sound and why rules are violated, and then discuss when a sound prediction may be made using these empirical VS rules. Graphical abstract: